Women and fertility behaviour - Choudhary, Kirti (Jaipur : Pointer Publishers : Distributed by Aavishkar Publishers, Distributors, 2012)
Study area Ajmer District, India.
Includes bibliographical references (p. [124]-141).
Keywords: Fertility, Human -- India -- Ajmer District; Pregnant women -- India -- Ajmer District -- Social life and customs; Birth control -- India -- Ajmer District